The Effectiveness of Using Interactive StoryMath Based on Articulate Storyline to Improve Mathematical Literacy in San Carlos Manlewana Elementary School - Harianingsih, Harianingsih; Raharjo, Tri Joko; Bunyamin, Bunyamin; Hidayati, Wiwik (Universitas Negeri Semarang, 2025)
This study aims to examine the effectiveness of using interactive StoryMath media based on Articulate Storyline in improving mathematical literacy of students at San Carlos Manlewana Elementary School. The background of this study is based on the low mathematical literacy skills of students which are still relatively low, as well as the need for more interesting, contextual, and interactive learning methods. This study used a quasi-experimental approach with a pretest-posttest design on 60 fifth grade students at San Carlos Manlewana Elementary School. Data were collected through mathematical literacy tests, observations, questionnaires, and teacher interviews. The results showed a significant increase in students' mathematical literacy scores after using StoryMath media, namely from an average of 58 in the pretest to 83 in the posttest. In addition, teachers reported that this media made it easier to convey abstract concepts, increase learning motivation, and active student participation during the learning process. Qualitative evaluation also revealed that students felt more interested and helped in understanding mathematical material through contextual and interactive stories. This finding is in line with the theory of experiential learning and the results of previous studies which confirm that interactive narrative-based learning media can improve student understanding and engagement. This study recommends the implementation of StoryMath media as an innovation in mathematics learning in elementary schools to support the development of effective and enjoyable mathematical literacy. The practical implications and further development of this media are also discussed as an effort to improve the quality of elementary education in the digital era.